Evaluation of the Financial Performance of Pension Funds. Empirical Evidence: Kosovo, Albania and North Macedonia - Mazreku, Ibish; Morina, Fisnik; Curraj, Elvis (European Journal of Sustainable Development, 2020)
Purpose: This research paper aims to analyze the evaluation of the financial performance of pension funds, to find the relationship between contributions, return on investment and net asset value with pension fund performance. The following research questions have been asked in order to realize the purpose of the research: What are the factors affecting the performance of the pension fund? What is the relationship between pension fund performance and contributions, return on investment, and net asset value? Methodology: For the specification of the econometric model of this study, we rely on secondary data published in official World Bank reports and reports of pension funds in Kosovo, Albania and North Macedonia. To measure the empirical results, these statistical tests are used: standard multiple regression, fixed effects model, random effect model, and Hausman Taylor Regression. Findings: Based on the empirical results, we can conclude that the increase in gross domestic product, return on investment, contributions and net assets have positively influenced the performance of pension funds for the countries included in the study. The other independent variable, the exchange rate, on the basis of econometric estimations, has turned out to be non-significant. Practical implications: The empirical results of this study may recommend that relevant institutions in Kosovo, Albania and North Macedonia undertake reforms towards the creation of efficient pension systems, and these reforms are of crucial importance for pension systems, which have an economic and social character in their function as fund accumulators and benefit distributors for the categories in need. Originality: The study is conducted with secondary data and all the empirical analysis are original based on the authors' calculations through econometric models. Through the results of this study we aim to provide additional empirical evidence on the performance of pension funds in Kosovo, Albania and North Macedonia, recommending that relevant institutions improve the functioning of the pension system, as it is a very important part of a financial system of a country which has an impact on economic growth. Keywords: financial performance, pension fund, contributions, net assets, return on investment